A Systematic Review of the Continuous Professional Development for Technology Enhanced Learning Literature - Williams, Ryan Thomas (Engineering International, 2020)
There is a large body of international research on raising the quality of education, with particular emphasis on CPD to support professional and pedagogical growth. From an educator’s perspective, there is widespread agreement that effective CPD is an important component of educational success. Therefore, it is unsurprising that research interest in this area has grown, particularly in light of the digital agenda. In a TEL context, educators report one of the main barriers to effective use is the lack of training in this area. This review of literature will examine some of the key ideas that form successful TEL CPD delivery, more specifically with relation to transformative models of CPD. Likewise, the section attempts to understand the context in which educators are operating and make sense of the challenges that relate to continuing professional development (CPD). In order to fully explore this phenomenon, personal development (PD) frameworks are explored, with a specific focus on Aileen Kennedy’s (2005) 9 typologies.